THE DEVELOPMENT OF ONLINE LESSON BY USING CASE-BASED LEARNING THAT ENHANCES DIGITAL INTELLIGENCE FOR VOCATIONAL CERTIFICATE STUDENT - Plengsri , Chalobol; Siripipattanakul, Sutithep; Rampai, Nattaphon (Journal of Educational Review Faculty of Education in MCU, 2024)
The objectives of this research are as follows: 1) To develop the online lessons by using case-based learning for enhances digital intelligence of vocational certificate student to be good quality level. 2) To study the results of enhances digital intelligence of vocational certificate student that are learned with online lessons by using case-based learning. 3) To compare the results of enhances digital intelligence of vocational certificate student that are learned with online lessons by using case-based learning with the criteria of 70 percent. 4) To study the satisfaction of student with online lessons by using case-based learning. The research followed an experimental approach, using the following research tools: 1) Lesson plan 2) Online lessons 3) Case studies 4) Post-test form 5) Quality assessment form 6) Satisfaction questionnaires. The statistics for data analysis, including mean and standard deviation (S.D.) and percentage. The research findings revealed: 1) Online lessons by using case-based learning for enhances digital intelligence of vocational certificate students that evaluated by content expert and media expert were a very good quality. 2) The results of strengthening digital intelligence found that the individual digital intelligence scores are between 70.61 - 81.52 percent, and group digital intelligence scores are between 73.08 - 88.46 percent, passed the standard criteria. 3) The results of comparing students’ digital intelligence with the criteria of 70 percent found that the students had an average individual digital intelligence accounting for 74.71 percent and the mean score for each group accounting for 80.23 percent, higher than the standard criteria that the researchers set at the .01 significance level, and 4) Students expressed the highest level of satisfaction with the online lessons by using case-based learning.